PEDAGOGICAL CONDITIONS FOR THE FORMATION OF READING CULTURE OF EDUCATION SEEKERS IN UKRAINIAN AND GLOBAL PRACTICE - Bilavych, Halyna; Bagriy, Maria; Klubochkina, Tetiana; Pantyuk, Mykola; Savchuk, Borys (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The aim of the article is to consider the formation of reading culture as an important pedagogical problem of today in the context of domestic and global problems of the development of students’ reading literacy, to single out the pedagogical conditions for the formation of the reading culture of an individual. Ukrainian and foreign scientists, teachers, and common people emphasize the crisis of children's reading: children and youth do not have a developed interest in this field of study, there is no motivation to read. This is a global trend. Pedagogical conditions for the formation of the reading culture of an individual are highlighted: from the teacher's point of view, this is high-quality preparation for teaching schoolchildren to read, mastery of a high level of reading culture, reading practice, children's reading circle; students believe that this is the activation of independent reading activity aimed at the development of abilities, interest in literature, improvement of knowledge, reading abilities and skills, active reading activity; parents think that it is the possession of reading culture, interest in reading, desire to ensure that fiction books do not lose their educational role among children, so that the great spiritual potential of fiction does not remain outside their attention, etc.